(untitled) (Altre Modernità, 2024)
Decolonial trajectories and anti-racist movements have engendered noteworthy transformations in the production of new literary and cultural archives, concurrently fostering fresh critical and theoretical perspectives. Since the 1970s, the emergence of Black movements in Brazil has fuelled the creation of substantial Afrodescendant literary works. From the 1990s onward, an analogous trend has manifested in the realm of indigenous literature, instigating a robust discourse on the significance, function, and characterisation of these literatures within the national canon. Within the Portuguese context, current generations of African post-memory are engrossed in forging decolonial paths intertwined with their distinctive literary and cultural creations, thereby challenging prevailing national literary impositions. Nevertheless, certain critical appraisals exhibit scepticism regarding the influence of these emergent literary archives, contending that excessive thematic content or overtly politicized stances compromise ‘literary quality.’ In light of these reflections, this article aims to scrutinize the interplay amongst these ‘minor literatures’ in Portuguese languages, elucidating their interconnections, mutual influences, and contributions towards unravelling the mythology of Lusophony and constructing spheres of linguistic occupation through a decolonial lens.